Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Pegawai di Biro Organisasi dan Kepegawaian Sekretariat Jenderal Kementerian Perdagangan - Sefriady, Dea Fanny (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
This research was aimed for knowing the influence between training and work discipline against the employeesâ performance of the Ministry of Trade. This research used a quantitative approach through survey to 50 employees. Sampling method is non probability sampling. Hypothesis test (t test) result that shows that the variable training affect significantly to these performance proved by t value about 2.501 which is more than t table. But the variable of work discipline do not affect significantly with t value about 0.042 which is less than t table.Â  The conclusion of this research is training is the most dominant variable over the performance of the employees. This means that increasing performance of the employees can be seen from the way the institutions provide compensation to employees.